Moxibustion for primary dysmenorrhea: A protocol for evidence-based clinical practice guideline. Issue 7 (19th February 2021) - Nie, Rongrong; Huang, Shouqiang; Liao, Weiye; Mao, Zhiming; Li, Xianglin; Xiong, Jun
Abstract: Background: Primary dysmenorrhea (PD) is a common gynecological disease characterized by lower abdominal pain. Moxibustion as a traditional Chinese treatment, can effectively treat PD with few adverse reactions. Nowadays, there is still no standard guideline for moxibustion treatment of PD, so related clinical practice guidelines need to be developed. Methods: This guideline will be developed in line with the latest guideline definition from Institute of Medicine, and that applies the GRADE system as well as the World Health Organization handbook to appraise the quality of evidence and develop recommendations. We will set up a Guideline working group, put forward the corresponding problems based on the principle of Population, Intervention, Comparison, Outcomes (PICO), and complete the literature retrieval. After achieving consensus through evidence syntheses and 2 to 3 rounds of Delphi process, we will also consider patients values and preferences and implement peer review in the guideline. Result: We will put forward evidence-based best practice recommendations and moxibustion standard to improve the symptoms caused by primary dysmenorrhea in a more efficient way. At present, the research is still in progress, and there is no result to report. Conclusions: This guideline will be helpful to clinical acupuncturists and other professionals to further improve clinical efficacy in treating PD with moxibustion. Moreover, we will also constantly update and evaluate the evidence to both support recommendations and identify gap areas for future research. Systematic Review registrations: registration number: IPGRP-2020CN021